Design of a Novel Fab‐Like Antibody Fragment with Enhanced Stability and Affinity for Clinical use. Issue 2 (28th November 2021) - Wang, Chunyu; Hong, Jiaxu; Yang, Zhenlin; Zhou, Xujiao; Yang, Yuhan; Kong, Yu; Chen, Binfan; Wu, Huifang; Qian, Bin‐Zhi; Dimitrov, Dimiter S.; Zhou, Xingtao; Wu, Yanling; et al.
Abstract: With increasing interest in applying recombinant monoclonal antibodies (mAbs) in human medicine, engineered mAb fragments with reduced size and improved stability are in demand to overcome current limitations in clinical use. Herein, a novel Fab‐like antibody fragment generated via an in silico‐based engineering approach where the CH1 and CL domains of Fab are replaced by the IgG1 CH3 domains is described. This construct, designated as FabCH3, maintains the natural N‐terminus and C‐terminus of IgG antibody, can be expressed at a high level in bacterial cells and, importantly, exhibits much higher stability and affinity than the parental Fab when tested in a mesothelin‐specific Fab m912, as well as a vascular endothelial growth factor A (VEGFA)‐specific Fab Ranibizumab (in vivo). The high‐resolution crystal structures of m912 FabCH3 and m912 Fab are determined, and the comparative analysis reveals more rigid structures in both constant domains and complementarity‐determining regions of FabCH3, explaining its enhanced stability and affinity. Overall, the stabilized FabCH3 described in this report provides a versatile platform for engineering Fab‐like antibody fragments with higher stability and antigen‐binding affinity that can be used as a distinct class of antibody therapeutics. Abstract : A novel approach to antibody design in which the CH1 and CL domains of Fab were replaced by the engineered IgG1 CH3 domains is provided. This novel Fab‐like antibody fragment, designated as FabCH3, has higher stability and antigen‐binding affinity than the parental Fab. The superior efficacy of FabCH3 over Fab has also been demonstrated in vivo.